Raising well-being in Germany's ageing society - Kappeler, Andreas (OECD Economics Department Working Papers, 2016)
Population ageing is setting in earlier in Germany than in most other OECD economies and will be marked. It could lead to a substantial decline in employment, weighing on GDP per capita, and will raise demand for health-related public services. Germany has already implemented far-reaching reforms to mitigate the implications of ageing for per capita income, well-being and the sustainability of public finances. Nonetheless, continued efforts are needed to help older workers to improve their work-life balance and adjust their working hours to their ability and desire to work. Moreover, stressful working conditions and unhealthy lifestyles contribute to poor self-reported health and reduce the ability and willingness to work at higher age. There is scope to promote life-long learning. As the generosity of the public pension system will diminish, the contribution of private pensions to ensure pension adequacy needs to be strengthened